Platelet indices in children with urinary tract infection - S., Srinivasa; Dhingra, Pragyee (International Journal of Contemporary Pediatrics, 2018)
Background: Urinary tract infection is one of the most common infection in children and may lead to serious morbidity like chronic pyelonephritis and renal scarring. Our hypothesis is that alteration of the platelet morphology can be a reliable index for early diagnosis and management of UTI without waiting for urine culture results. We try to demonstrate a link between the platelet indices and the type of organism, whether gram positive or gram negative to allow proper selection of the antibiotic regimen. Methods: It is a retrospective case control study where 35 urine culture proven cases and 35 cases of non UTI cases was taken as control. Children with haematological diseases affecting platelet were excluded. Platelet indices were taken including for MPV, PDW and platelet count and statistically analysed. Results: MPV and PDW were higher in patient with culture proven especially with gram positive organism. Conclusions: Although urine culture is considered as golden standard for diagnosis of urinary culture, it is time consuming. But early diagnosis can prevent renal parenchymal complications. Hence, we tried to find out other early, easy and sensitive method for detection of urinary tract infections in children. Platelet parameters (thrombocytosis, mean platelet volume, platelet distribution width) is available in analyser report of any complete blood count with no added value. It was also found that gram positive organism has higher mean platelet volume and platelet distribution width as compared to gram negative organism.